PENDIDIKAN ETNIS TIONGHOA DI KOTA MAKASSAR - irwan, irwan (FAJAR HISTORIA: Jurnal Ilmu Sejarah dan Pendidikan, 2018)
This study aims to investigate the influence of character formation in environmental education ethnic Chinese family in the city of Makassar, the role of teachers in the school environment, and efforts to maintain the culture of Chinese ethnic studies. This study used a descriptive approach qualitative data collection techniques, observation, interviews, and observations. Through the results showed that, education environment ethnic Chinese families in the process of guiding, teaching, and training were influenced family circumstances. The role of parents is very influential in implementing and running a learning culture that taught the value of Chinese ethnic ancestry. The teacher's role in guiding the cultural values of ethnic Chinese are not optimally obtained in the school environment. This is due to the absence of a special school in Makassar ethnic Chinese. In the process of the social life of the Chinese people has always maintained a culture that will continue to exist and survive in the community are the majority so that they retain their culture. By continuing to learn traditional Chinese people, this is what makes the Chinese people to survive until today.Key Words : Education, Ethnicity, Culture